Screening of Inhibitors against Multidrug Resistant Protein 1 through Molecular Docking - Dabbikar, Shiroli; Jaipuriar, Dipti Soni; Y, Sabitha (Asian Journal of Biological and Life Sciences)
Multidrug Resistant Protein 1 (MRP1) has a significant role in the expulsion of substrates from the cancer cell. The over expression of MRP1 can be a reason for the unsuccessful attempt in chemotherapy. This study aims to find compounds that have an inhibitory role against MRP1 through Molecular Docking. Molecular Docking helps in visual analysis of the interactions between the ligand and a macromolecular target. The domain structure of MRP1 (PDB ID: 2CBZ) was retrieved from RCSB PDB and was visualized on UCSF Chimera. 58429 compounds were withdrawn from ChEBI and the ADMET parameters of 15178 selected compounds were evaluated by SwissADME predictor. The Primary and Secondary docking analysis was performed on Igemdock and AutoDock Vina respectively. Five compounds with low binding energies were selected from the results generated by Igemdock and they were subjected to secondary docking program on AutoDock Vina. From the binding energy and docking score outcomes of primary and secondary docking analysis we concluded that Acrivastine is the best candidate for targeting MRP1.
Keywords: AutoDock Vina; Binding Affinity; Igemdock; Molecular docking; Multidrug Resistant Protein 1